Approaches to correcting errors in the teaching of the English language - Dilrabo Safarova Kholmurodovna (Euro Asian Journal Publishing, 2024)
This study investigates diverse methodologies employed for error correction in English language instruction. Drawing on an examination of literature and interviews with educators, the research delineates effective approaches such as direct correction, feedback delivery, and cultivating a supportive learning ambiance. The findings underscore the significance of adopting a well-rounded strategy that integrates these methods to enhance language acquisition and proficiency
Keywords: Error correction; English language teaching; English language teachingEnglish language teaching